Efek Ekstrak Etanol Daun Premna cordifolia terhadap Malondialdehida Tikus yang Dipapar Asap Rokok - Adyttia, Asri; Untari, Eka Kartika; Wahdaningsih, Sri (UI Scholars Hub, 2014)
Free radical from cigarrete smoke cause lipid peroxidation that could be identified by increasing levels of Malondialdehida (MDA). Premna cordifolia leaves known having antioxidant activity in in vitro study. This study aimed to know the effect of P. cordifolia leaves extract on the levels of MDA after exposure to cigarette smoke. The simplicia extracted by maseration using 70% ethanol. Twenty four male wistar rats were divided into six groups, i.e. : control normal, negative control, positive control received cigarette smoke exposure and vitamin E (18mg/kg BW) and three groups received cigarette smoke exposure and P. cordifolia leaves extract with doses 200; 400; 600 mg/kg BW. All rats were treated for 14 days. Measurement of MDA level using Spectrophotometer UV-Vis in 532,2 nm. MDA levels in the normal group was 0.0094±0.080 ppm; negative group was 13,733±2,829 ppm; positive group was 0,051±0,045 ppm; dose 200; 400; 600 mg/kg BW were 9,142±2,364; 0,120±0,019; 0,053±0,041 ppm. The MDA level was analyzed by the Kruskal-Wallis test and following by Mann-Whitney test. The result showed that MDA level of group receiving P. cordifolia leaves extract significantly (p < 0,05) lower than negative control group. These result show P. cordifolia leaves extract can reducing the MDA level on the rats that exposed by cigarette smoke.